Multi-element modified crystalline sulfide-based solid electrolyte and all-solid-state battery

By using multi-element modified crystalline sulfide-based solid electrolyte in all-solid state batteries, combining sulfide solid electrolyte and metal oxide quantum dots, the poor safety and stability of traditional liquid batteries are solved, and a higher level of safety is achieved battery performance and safety.

CN119153766AInactive Publication Date: 2024-12-17ZHONGKE RONNENG (YANCHENG) TECH CO LTD

Patent Information

Application Number
CN202411406314.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional liquid lithium-ion batteries have problems such as poor safety performance, low energy density, and narrow operating temperature range. The poor stability and low ionic conductivity of sulfide solid electrolytes limit the practical application of all-solid-state batteries.

Method used

Using multi-element modified crystalline sulfide-based solid electrolytes, including a core layer and a hydrophobic material layer coated on the outer surface of the core layer, the core layer contains sulfide solid electrolyte particles and metal oxide quantum dots distributed therein, through Preparation is carried out by ball milling, heat treatment and sintering steps to improve the ionic conductivity and stability of the electrolyte.

Benefits of technology

It significantly improves the overall performance of all-solid-state batteries, improves the safety and reliability of the battery, improves the theoretical specific capacity and voltage window of the negative electrode, inhibits the growth of lithium dendrites, and solves the safety problems of traditional liquid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153766A_ABST
    Figure CN119153766A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-element modified crystalline sulfide-based solid electrolyte, which comprises a core layer and a hydrophobic material layer coated on the outer surface of the core layer, and relates to the technical field of lithium ion batteries. According to the multi-element modified crystalline sulfide-based solid-state electrolyte and the all-solid-state battery, the ionic conductivity of the sulfide solid-state electrolyte is effectively improved by introducing the metal oxide quantum dots, the overall performance of the battery is improved, and the lattice stability of the sulfide solid-state electrolyte is enhanced by adding the metal oxide quantum dots; the lithium magnesium alloy is adopted as the negative electrode, the theoretical specific capacity and the voltage window of the negative electrode are improved, meanwhile, the impedance of the negative electrode and an electrolyte interface is improved, the growth of lithium dendrites is inhibited, the all-solid-state battery does not contain a liquid electrolyte, and the safety problem of a traditional liquid-state battery is fundamentally solved; and the safety and the reliability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, in particular to a multi-element modified crystalline sulfide-based solid electrolyte and an all-solid-state battery. Background Art

[0002] Lithium-ion batteries, commonly known as rocking chair batteries, are a general term for batteries with lithium-ion embedded compounds as positive electrode materials. They are a type of secondary battery that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. Lithium-ion batteries are composed of positive and negative electrodes, electrolytes and separators, plus positive and negative leads, battery shells, safety devices, etc. During the charging and discharging process of lithium-ion batteries, Li+ is embedded and deintercalated back and forth between the two electrodes: during charging, Li+ is deintercalated from the positive electrode and embedded into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; during discharging, the opposite is true. Mobile phones and laptops all use lithium-ion batteries, which are usually commonly referred to as lithium batteries. Petroleum coke and graphite are non-toxic and abundant in resources as negative electrode materials. Lithium ions are embedded in carbon, which overcomes the high activity of lithium and solves the safety problems of traditional lithium batteries. The positive electrode LixCoO2 can achieve a high level in charging and discharging performance and life, reducing costs. In short, the comprehensive performance of lithium-ion batteries has been improved.

[0003] Traditional liquid batteries contain a large amount of organic flammable liquid electrolytes, so they have defects such as poor safety performance, low energy density, and narrow operating temperature range. In contrast, all-solid-state batteries do not contain liquid substances, so they have significant advantages in safety, energy density, cycle life, and electrochemical window. As a key component of all-solid-state batteries, the performance of solid electrolytes directly determines the overall performance of the battery. Sulfide solid electrolytes have broad application prospects in electric vehicles, portable devices, and other fields due to their high ionic conductivity, wide electrochemical window, and cold pressing. However, sulfide solid electrolytes have problems such as poor stability and low ionic conductivity, which limit their practical applications. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a multi-element modified crystalline sulfide-based solid electrolyte and an all-solid-state battery, which solve the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a multi-element modified crystalline sulfide-based solid electrolyte, including a core layer and a hydrophobic material layer coated on the outer surface of the core layer, the core layer includes a plurality of sulfide solid electrolyte particles and metal oxide quantum dots distributed between the sulfide solid electrolyte particles.

[0006] Preferably, the metal element in the metal oxide quantum dots is selected from one or more of Group IIIA, Group VIII, Group IVB, and Group VIIB elements, preferably SnO2, MnO, CoO, Fe2O3 or TiO2 quantum dots.

[0007] Preferably, the sulfide solid electrolyte particles are selected from one or more of Li7-xPS6-xClx particles, where 0.6≤x≤1.9, preferably Li6PS5Cl particles.

[0008] Preferably, in the core layer, the weight ratio of the sulfide solid electrolyte particles to the metal oxide quantum dots is 1:(0.15-0.7).

[0009] Preferably, the preparation method of the multi-element modified crystalline sulfide-based solid electrolyte specifically comprises the following steps:

[0010] S1. Preparation of raw materials: According to the chemical formula of the target sulfide-based solid electrolyte, select the corresponding sulfide, halide, etc. as raw materials. For sulfide solid electrolytes such as Li6PS5Cl, it is necessary to prepare Li2S, P2S5 and LiCl raw materials;

[0011] S2, mixing and ball milling: mixing the selected raw materials in a certain molar ratio to ensure uniform mixing, mixing the sulfide solid electrolyte particles and the metal oxide quantum dots and ball milling them, the ball milling speed is 200 to 500 r / min, and the ball milling time is 3 to 10 hours;

[0012] S3, modification treatment: During the ball milling process, modifying elements are introduced into the mixture. These modifying elements can be metal oxide quantum dots, SnO2, MnO, CoO, which can modify the electrolyte by improving the ionic conductivity of the solid electrolyte and enhancing the air stability, ensuring that the modifying elements are fully mixed with the sulfide-based solid electrolyte particles;

[0013] S4, heat treatment and sintering: the uniformly mixed powder is pre-sintered and calcined at 800-1000°C for 10-15 hours to remove some volatile impurities and initially form the crystal structure of the solid electrolyte. In order to improve the crystallinity and density of the solid electrolyte, a secondary sintering process is used;

[0014] S5. Post-processing and characterization: The sintered solid electrolyte is subjected to necessary post-processing, such as grinding and screening, to obtain electrolyte powder or sheets that meet the requirements. The prepared solid electrolyte is characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), etc. to confirm its parameters such as crystal structure, morphology and performance.

[0015] Preferably, in S2, a high-energy ball mill is used to ball-mill the mixed raw materials. During the ball-milling process, the raw material particles are refined by the action of mechanical force, and the mixing and reaction between the raw materials are promoted. In S4, the electrolyte sheet obtained by pre-sintering is crushed and ground into a powder, then pressed again and sintered at a slightly higher temperature. The secondary sintering helps to homogenize the grain size and improve the performance of the electrolyte.

[0016] The present invention also discloses a all-solid-state battery, which includes a positive electrode layer, a negative electrode layer, and a multi-element modified crystalline sulfide-based solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The negative electrode layer is made of a lithium-magnesium alloy, and the mass ratio of magnesium metal in the lithium-magnesium alloy is 1.4% to 6%, preferably 4%. The positive electrode layer is composed of an active material, a conductive agent, and a sulfide solid electrolyte. The active material can be LiNi_xCo_yMn_zO_2 or LiNi_xCo_yAl_zO_2, where 0 < x < 1, 0 < y < 1, and x + y + z = 1. The conductive agent is one or more of graphite, graphene, carbon nanotubes, acetylene black, or Super P.

[0017] Preferably, the preparation method of the all-solid-state battery specifically includes the following steps:

[0018] S1. Press the multi-element modified crystalline sulfide-based solid electrolyte powder into an electrolyte sheet;

[0019] S2. Mix the positive electrode active material, the conductive agent, and the solid electrolyte powder, spread them on one side of the electrolyte sheet, and press them into a positive electrode layer;

[0020] S3. Place the lithium-magnesium alloy on the other side of the electrolyte sheet and press it into a negative electrode layer to obtain the all-solid-state battery.

[0021] Beneficial effects

[0022] The present invention provides a multi-element modified crystalline sulfide-based solid electrolyte and an all-solid-state battery. Compared with the prior art, the multi-element modified crystalline sulfide-based solid electrolyte and the all-solid-state battery have the following beneficial effects: the multi-element modified crystalline sulfide-based solid electrolyte and the all-solid-state battery include a core layer and a hydrophobic material layer coated on the outer surface of the core layer, the core layer includes a plurality of sulfide solid electrolyte particles and metal oxide quantum dots distributed between the sulfide solid electrolyte particles, the metal elements in the metal oxide quantum dots are selected from one or more of the elements of Group IIIA, Group VIII, Group IVB, and Group VIIB, preferably SnO2, MnO, CoO, Fe2O3 or TiO2 quantum dots, the sulfide solid electrolyte particles are selected from one or more of the particles of Li7-xPS6-xClx, wherein 0.6≤x≤1.9, preferably L In the core layer of i6PS5Cl particles, the weight ratio of sulfide solid electrolyte particles and metal oxide quantum dots is 1:(0.15-0.7). The introduction of metal oxide quantum dots effectively improves the ionic conductivity of the sulfide solid electrolyte and improves the overall performance of the battery. The addition of metal oxide quantum dots enhances the lattice stability of the sulfide solid electrolyte and improves its stability in a humid environment. Lithium-magnesium alloy is used as the negative electrode to improve the theoretical specific capacity and voltage window of the negative electrode. At the same time, the impedance of the interface between the negative electrode and the electrolyte is improved, and the growth of lithium dendrites is inhibited. The all-solid-state battery does not contain liquid electrolyte, which fundamentally solves the safety problem of traditional liquid batteries and improves the safety and reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] See also Figure 1 The present invention provides three technical solutions: a multi-element modified crystalline sulfide-based solid electrolyte, comprising a core layer and a hydrophobic material layer coated on the outer surface of the core layer, wherein the core layer comprises a plurality of sulfide solid electrolyte particles and metal oxide quantum dots distributed between the sulfide solid electrolyte particles.

[0026] In the present invention, the metal element in the metal oxide quantum dots is selected from one or more of the elements of Group IIIA, Group VIII, Group IVB, and Group VIIB, and is preferably SnO2, MnO, CoO, Fe2O3 or TiO2 quantum dots.

[0027] In the present invention, the sulfide solid electrolyte particles are selected from one or more of Li7-xPS6-xClx particles, where 0.6≤x≤1.9, preferably Li6PS5Cl particles.

[0028] In the present invention, in the core layer, the weight ratio of the sulfide solid electrolyte particles to the metal oxide quantum dots is 1:(0.15-0.7).

[0029] In the present invention, a method for preparing a multi-element modified crystalline sulfide-based solid electrolyte specifically includes the following embodiments:

[0030] Embodiment 1

[0031] S1. Preparation of raw materials: According to the chemical formula of the target sulfide-based solid electrolyte, select the corresponding sulfide, halide, etc. as raw materials. For sulfide solid electrolytes such as Li6PS5Cl, it is necessary to prepare Li2S, P2S5 and LiCl raw materials;

[0032] S2, mixing and ball milling: the selected raw materials are mixed in a certain molar ratio to ensure uniform mixing, and the sulfide solid electrolyte particles and the metal oxide quantum dots are mixed and ball milled at a ball milling speed of 350 r / min for 6 hours;

[0033] S3, modification treatment: During the ball milling process, modifying elements are introduced into the mixture. These modifying elements can be metal oxide quantum dots, SnO2, MnO, CoO, which can modify the electrolyte by improving the ionic conductivity of the solid electrolyte and enhancing the air stability, ensuring that the modifying elements are fully mixed with the sulfide-based solid electrolyte particles;

[0034] S4, heat treatment and sintering: the uniformly mixed powder is pre-sintered at 900°C for 13 hours to remove some volatile impurities and initially form the crystal structure of the solid electrolyte. In order to improve the crystallinity and density of the solid electrolyte, a secondary sintering process is used;

[0035] S5. Post-processing and characterization: The sintered solid electrolyte is subjected to necessary post-processing, such as grinding and screening, to obtain electrolyte powder or sheets that meet the requirements. The prepared solid electrolyte is characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), etc. to confirm its parameters such as crystal structure, morphology and performance.

[0036] Embodiment 2

[0037] S1. Preparation of raw materials: According to the chemical formula of the target sulfide-based solid electrolyte, select the corresponding sulfide, halide, etc. as raw materials. For sulfide solid electrolytes such as Li6PS5Cl, it is necessary to prepare Li2S, P2S5 and LiCl raw materials;

[0038] S2, mixing and ball milling: the selected raw materials are mixed according to a certain molar ratio to ensure uniform mixing, and the sulfide solid electrolyte particles and the metal oxide quantum dots are mixed and ball milled at a ball milling speed of 200 r / min for 3 hours;

[0039] S3, modification treatment: During the ball milling process, modifying elements are introduced into the mixture. These modifying elements can be metal oxide quantum dots, SnO2, MnO, CoO, which can modify the electrolyte by improving the ionic conductivity of the solid electrolyte and enhancing the air stability, ensuring that the modifying elements are fully mixed with the sulfide-based solid electrolyte particles;

[0040] S4, heat treatment and sintering: the uniformly mixed powder is pre-sintered at 800°C for 10 hours to remove some volatile impurities and initially form the crystal structure of the solid electrolyte. In order to improve the crystallinity and density of the solid electrolyte, a secondary sintering process is used;

[0041] S5. Post-processing and characterization: The sintered solid electrolyte is subjected to necessary post-processing, such as grinding and screening, to obtain electrolyte powder or sheets that meet the requirements. The prepared solid electrolyte is characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), etc. to confirm its parameters such as crystal structure, morphology and performance.

[0042] Embodiment 3

[0043] S1. Preparation of raw materials: According to the chemical formula of the target sulfide-based solid electrolyte, select the corresponding sulfide, halide, etc. as raw materials. For sulfide solid electrolytes such as Li6PS5Cl, it is necessary to prepare Li2S, P2S5 and LiCl raw materials;

[0044] S2, mixing and ball milling: the selected raw materials are mixed in a certain molar ratio to ensure uniform mixing, and the sulfide solid electrolyte particles and the metal oxide quantum dots are mixed and ball milled at a ball milling speed of 500 r / min for 10 hours;

[0045] S3, modification treatment: During the ball milling process, modifying elements are introduced into the mixture. These modifying elements can be metal oxide quantum dots, SnO2, MnO, CoO, which can modify the electrolyte by improving the ionic conductivity of the solid electrolyte and enhancing the air stability, ensuring that the modifying elements are fully mixed with the sulfide-based solid electrolyte particles;

[0046] S4, heat treatment and sintering: the uniformly mixed powder is pre-sintered at 800-1000°C for 15 hours to remove some volatile impurities and initially form the crystal structure of the solid electrolyte. In order to improve the crystallinity and density of the solid electrolyte, a secondary sintering process is used;

[0047] S5. Post-processing and characterization: The sintered solid electrolyte is subjected to necessary post-processing, such as grinding and screening, to obtain electrolyte powder or sheets that meet the requirements. The prepared solid electrolyte is characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), etc. to confirm its parameters such as crystal structure, morphology and performance.

[0048] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0049] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0050] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A multi-element modified crystalline sulfide-based solid electrolyte, comprising a core layer and a hydrophobic material layer coated on the outer surface of the core layer, characterized in that: The core layer includes a plurality of sulfide solid electrolyte particles and metal oxide quantum dots distributed between the sulfide solid electrolyte particles.

2. A multi-element modified crystalline sulfide-based solid electrolyte according to claim 1, characterized in that: The metal element in the metal oxide quantum dots is selected from one or more of Group IIIA, Group VIII, Group IVB, and Group VIIB elements, preferably SnO2, MnO, CoO, Fe2O3 or TiO2 quantum dots.

3. A multi-element modified crystalline sulfide-based solid electrolyte according to claim 1, characterized in that: The sulfide solid electrolyte particles are selected from one or more of Li7-xPS6-xClx particles, where 0.6≤x≤1.9, preferably Li6PS5Cl particles.

4. A multi-element modified crystalline sulfide-based solid electrolyte according to claim 1, characterized in that: In the core layer, the weight ratio of the sulfide solid electrolyte particles to the metal oxide quantum dots is 1:(0.15-0.7).

5. The multi-element modified crystalline sulfide-based solid electrolyte according to claim 1, characterized in that: The preparation method specifically comprises the following steps: S1. Preparation of raw materials: According to the chemical formula of the target sulfide-based solid electrolyte, select the corresponding sulfide, halide, etc. as raw materials. For sulfide solid electrolytes such as Li6PS5Cl, it is necessary to prepare Li2S, P2S5 and LiCl raw materials; S2, mixing and ball milling: mixing the selected raw materials in a certain molar ratio to ensure uniform mixing, mixing the sulfide solid electrolyte particles and the metal oxide quantum dots and ball milling them, the ball milling speed is 200 to 500 r / min, and the ball milling time is 3 to 10 hours; S3, modification treatment: During the ball milling process, modifying elements are introduced into the mixture. These modifying elements can be metal oxide quantum dots, SnO2, MnO, CoO, which can modify the electrolyte by improving the ionic conductivity of the solid electrolyte and enhancing the air stability, ensuring that the modifying elements are fully mixed with the sulfide-based solid electrolyte particles; S4, heat treatment and sintering: the uniformly mixed powder is pre-sintered and calcined at 800-1000°C for 10-15 hours to remove some volatile impurities and initially form the crystal structure of the solid electrolyte. In order to improve the crystallinity and density of the solid electrolyte, a secondary sintering process is used; S5. Post-processing and characterization: The sintered solid electrolyte is subjected to necessary post-processing, such as grinding and screening, to obtain electrolyte powder or sheets that meet the requirements. The prepared solid electrolyte is characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), etc. to confirm its parameters such as crystal structure, morphology and performance.

6. The multi-element modified crystalline sulfide-based solid electrolyte according to claim 1, characterized in that: In S2, a high-energy ball mill is used to ball-mill the mixed raw materials. During the ball-milling process, the raw material particles are refined by the action of mechanical force, and the mixing and reaction between the raw materials are promoted. In S4, the electrolyte sheet obtained by pre-sintering is crushed and ground into powder, and then pressed again and sintered at a slightly higher temperature. The secondary sintering helps to homogenize the grain size and improve the performance of the electrolyte.

7. An all-solid-state battery, characterized in that: The all-solid-state battery includes a positive electrode layer, a negative electrode layer, and a multi-element modified crystalline sulfide-based solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The negative electrode layer is made of a lithium-magnesium alloy, and the mass ratio of magnesium metal in the lithium-magnesium alloy is 1.4% to 6%, preferably 4%. The positive electrode layer is composed of an active material, a conductive agent, and a sulfide solid electrolyte. The active material can be LiNi_xCo_yMn_zO_2 or LiNi_xCo_yAl_zO_2, where 0 < x < 1, 0 < y < 1, and x + y + z = 1. The conductive agent is one or more of graphite, graphene, carbon nanotubes, acetylene black, or Super P.

8. The all-solid-state battery according to claim 1, characterized in that: Its preparation method specifically includes the following steps: S1. Press the multi-element modified crystalline sulfide-based solid electrolyte powder into an electrolyte sheet. S2. Mix the positive electrode active material, the conductive agent, and the solid electrolyte powder, spread them on one side of the electrolyte sheet, and press them into a positive electrode layer. S3. Place the lithium-magnesium alloy on the other side of the electrolyte sheet and press it into a negative electrode layer to obtain the all-solid-state battery.

Citation Information

Patent Citations

  • Preparation method of sulfide solid electrolyte

    CN114421003A

  • Sulfide solid electrolyte, preparation method thereof and all-solid-state lithium ion battery

    CN115579511A

  • Modified sulfide solid electrolyte, preparation method thereof and all-solid-state battery

    CN116505059A

  • Sulfide all-solid-state battery and preparation method thereof

    CN117154012A

  • Solid electrolyte membrane, preparation method therefor, use thereof, and solid-state battery

    WO2024141028A1

Cited By

  • Composite sulfide solid electrolyte material, preparation method and application

    CN119551637A

  • A composite sulfide solid electrolyte material, preparation method and application

    CN119551637B